Sustainable roof selection: Environmental and contextual factors to be considered in choosing a vegetated roof or rooftop solar photovoltaic system. (November 2017) - Dimond, Kirk; Webb, Amy
Highlights: We compare cited benefits from 121 articles for vegetated roofs and solar PV systems. Nine classifications of sustainability emerged from the literature. Findings suggest that systems obtain the greatest benefit when part of a broader network. We propose a classification of system impacts based on three scales of consideration to facilitate comparison. Abstract: Vegetated roofs and roof top Solar Photovoltaic (PV) systems are both commonly accepted as sustainable roofing systems and compete for space and budget in building projects. However, the two systems are quite different in composition and purpose, making it difficult to compare which system would be the most appropriate solution. While much research has been conducted on the efficiencies of each system separately, limited literature directly compares the two by highlighting the similarities and differences in their environmental benefits and contextual needs. This study reviews the existing literature of both solar PV and vegetated roof performance, and proposes a classification of considerations to facilitate their comparison. Current peer reviewed literature is collated and synthesized for comparison based on the emergence of nine shared categories of cited performance, relating to Aesthetics, Ecology, Energy, and Water. The literature is further analyzed to classify the considerations of each category based on an associated scale of analysis, including site, landscape and regional opportunities and concerns. By framing the performance of these roofing systems in this way, the comparison of the two systems can be fitted to the type and scale of unique project goals and challenges to facilitate analysis and decision-making.